2005
DOI: 10.1016/j.pain.2005.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathic pain: Early spontaneous afferent activity is the trigger

Abstract: Intractable neuropathic pain often results from nerve injury. One immediate event in damaged nerve is a sustained increase in spontaneous afferent activity, which has a well-established role in ongoing pain. Using two rat models of neuropathic pain, the CCI and SNI models, we show that local, temporary nerve blockade of this afferent activity permanently inhibits the subsequent development of both thermal hyperalgesia and mechanical allodynia. Timing is critical-the nerve blockade must last at least 3-5 days a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
161
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(180 citation statements)
references
References 52 publications
10
161
0
3
Order By: Relevance
“…3C), our data suggest that new cortical connections are rapidly generated after neuro-pathic injury with simultaneous, but relatively slow, elimination of preexisting circuits, followed by refinement of the new connections. Because early afferent hyperactivity is the key driver for development of CNS changes and allodynia (Devor, 2006), we conducted local blockade of the injured nerve throughout the early phase, which prevents afferent ectopic firing even after its action is finished (Xie et al, 2005), by directly implanting an Elvax-TTX immediately after PSL. Such temporary blockade prevented the increase of spine gain and loss in the S1 ( p Ͼ 0.3) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3C), our data suggest that new cortical connections are rapidly generated after neuro-pathic injury with simultaneous, but relatively slow, elimination of preexisting circuits, followed by refinement of the new connections. Because early afferent hyperactivity is the key driver for development of CNS changes and allodynia (Devor, 2006), we conducted local blockade of the injured nerve throughout the early phase, which prevents afferent ectopic firing even after its action is finished (Xie et al, 2005), by directly implanting an Elvax-TTX immediately after PSL. Such temporary blockade prevented the increase of spine gain and loss in the S1 ( p Ͼ 0.3) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…immediately/first few days following induction of peripheral neuropathy) of nerve injury (Araujo et al, 2003;Gonzalez-Darder et al, 1986;Lindia et al, 2005;Seltzer et al, 1991a;Sotgiu et al, 1994;Sotgiu et al, 1995b;Xie et al, 2005Xie et al, , 2007Yamamoto et al, 1993), but see Suter et al (2003). Xie et al (2005) reported that blocking peripheral nerve input during the first five days after model induction permanently prevents development of pain-like behavior. Despite important short-term effects of nerve injury, in the light of our present results peripheral drive (≥2 weeks after induction of neuropathy) must nonetheless be seen as being important in the later maintenance phase of other models of peripheral neuropathy.…”
Section: Contribution Of Peripheral Drive In Early and Late Stages Ofmentioning
confidence: 99%
“…One hypothesis suggests that central sensitization at the level of the spinal dorsal horn is maintained independently of primary afferent input (Sandkuhler and Liu, 1998) since input from the periphery is reportedly insufficient to maintain spinal modifications in sensory processing and ultimately neuropathic pain (Burgess et al, 2002;Sun et al, 2005;Xie et al, 2005). Another view suggests that mechanisms at the spinal dorsal horn level require continuous facilitatory input from supraspinal structures Carlson et al, 2007;Gardell et al, 2003;Kauppila et al,1998;Kovelowski et al, 2000;Ossipov et al, 2000;Pertovaara et al, 1997Pertovaara et al, , 2001Porreca et al, 2001;Saade et al, 2006aSaade et al, ,b, 2007Suzuki et al, 2002Suzuki et al, , 2004aVeraPortocarrero et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…[143][144][145] Experimental evidence and clinical experiences in human medicine indicate that central hyperalgesia can be obliterated by no other treatment modality as effectively as by loco-regional anesthesia and analgesia aimed at interrupting or diminishing impulse trafficking from the site of tissue injury to the CNS and within the dorsal horn of the spinal cord. 56,59,78,[143][144][145][146][147] Those techniques may include wound infiltration or joint injections with local anesthetics, topical local anesthetic application using lidocaine patches, repetitive or even better continuous peripheral nerve blocks, and epidural or intrathecal anesthesia and analgesia.…”
Section: Loco-regional Anesthesia and Analgesiamentioning
confidence: 99%